Anxieties of Seeing: The Sensational World of Cinema, Digital Media and Politics. (December 2018) - Mokkil, Navaneetha
This article analyses the super-hit Malayalam film Drishyam (Sight) in relation to the modalities of protest in the Chumbanasamaram (Kiss of Love [KoL] campaign) in 2014 in Kerala in which the kiss was deployed as a form of public protest. It brings together a popular thriller and a political protest that made waves in the entire nation in order to explore how shifting media technologies choreograph performative modes of doing politics. Drishyam stages the convergence of different media forms and legitimises the conventions of older forms such as cinema that hinges on the spectacle of women's bodies and sexual acts on screen. At the same time, digital technology and the modes of circulation and reception it facilitates function as a node of heightened anxiety. Although Drishyam precedes the KoL campaign, this film can be seen as a response to precisely the (hyper) visibility of bodies and sexuality in the public domain through the workings of new media technologies. The film is driven by an overwhelming concern about the public performance of intimacy—contiguous with the secret filming and the threat of circulation of the naked woman's body that is the cause of crisis in the film. Thus, I argue that the energies that drive Drishyam and finds a resonance with a national audience, in fact, anticipates KoL-type display of sexuality which is at once unauthorised and out of place but also mediated by unruly technologies.